Pelaksanaan Hukum Pidana Dalam Konteks Pertanggungjawaban Pidana Untuk Pelaku Eksibisionisme - Namora, Mohammad Satria; Barraphindo Raseto; Muhammad Dirgantara Wibawa; Wahyu Adi Ramadhani; Liza Deshaini (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
The phenomenon of exhibitionism in Indonesia is increasingly concerning because it can occur in various public spaces such as public transportation, highways, and even live broadcasts on social media. How is criminal law implemented in the context of criminal liability for perpetrators of exhibitionism? This research uses normative (normative juridical) research with a legislative and conceptual approach. In conclusion, exhibitionism is considered a criminal offense and is regulated by the Criminal Code and the Pornography Law. The Pornography Law (Law No. 44 of 2008) strengthens criminal sanctions against exhibitionism. Article 10 of the Pornography Law implicitly defines exhibitionism as displays of nudity or pornographic content in public places. Although the term